Discovery Learning in Maharah Qira’ah: A Qualitative Study Based on Bruner’s Cognitive Theory at an Islamic University in Indonesia - Miftahul Mufid; Isnainiyah; Nurul Ainiy (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: This study aims to describe the implementation of maharah qirah (reading skills) learning using the Discovery Learning model at the Arabic Language Development Center (PPBA), University of Muhammadiyah Malang, Indonesia. Methodology: This research adopts a qualitative approach with a case study design. Data were collected through observation and documentation, with the researcher serving as the primary instrument, directly involved in understanding behaviors, interactions, and the contextual learning environment. Field notes and supporting documents were used to enrich the data. Findings: The findings indicate that the application of Discovery Learning, based on Jerome Bruner’s cognitive theory, follows several systematic stages: stimulation, problem formulation, data collection, data processing, verification, and generalization. The results demonstrate that students are able to learn independently, formulate hypotheses, explore the meaning of texts in depth, and derive contextual conclusions from reading materials, thereby connecting academic content to real-life experiences. Implications/Novel Contribution: The Discovery Learning model has many important benefits in the educational process, namely increasing learning independence, enhancing understanding of concepts, increasing motivation and interest in learning, developing social skills, encouraging critical thinking processes, enhancing curiosity, and facilitating problem-based learning.